Anti-money laundering and counter financing of terrorism law in Malaysia - Mohd Yasin, Norhashimah; Zul Kepli, Mohd Yazid (LexisNexis, 2018)
This book is a concise, accessible and practical guide to compliance with Anti-Money Laundering and Counter Financing of Terrorism (AML/CFT) laws in Malaysia for Reporting Institutions.